Paul's three paths to salvation - Boccaccini, Gabriele 1958- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2020)
"A historical argument that Paul's teachings suggest three different methods of salvation"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Theology; Salvation -- Biblical teaching